Adaptation and validation of the Alzheimer's Disease Assessment Scale – Cognitive (ADAS-Cog) in a low-literacy setting in sub-Saharan Africa. Issue 4 (27th March 2017) - Paddick, Stella-Maria; Kisoli, Aloyce; Mkenda, Sarah; Mbowe, Godfrey; Gray, William Keith; Dotchin, Catherine; Ogunniyi, Adesola; Kisima, John; Olakehinde, Olaide; Mushi, Declare; Walker, Richard William
Abstract : Objective: This study aimed to assess the feasibility of a low-literacy adaptation of the Alzheimer's Disease Assessment Scale – Cognitive (ADAS-Cog) for use in rural sub-Saharan Africa (SSA) for interventional studies in dementia. No such adaptations currently exist. Methods: Tanzanian and Nigerian health professionals adapted the ADAS-Cog by consensus. Validation took place in a cross-sectional sample of 34 rural-dwelling older adults with mild/moderate dementia alongside 32 non-demented controls in Tanzania. Participants were oversampled for lower educational level. Inter-rater reliability was conducted by two trained raters in 22 older adults (13 with dementia) from the same population. Assessors were blind to diagnostic group. Results: Median ADAS-Cog scores were 28.75 (interquartile range (IQR), 22.96–35.54) in mild/moderate dementia and 12.75 (IQR 9.08–16.16) in controls. The area under the receiver operating characteristic curve (AUC) was 0.973 (95% confidence interval (CI) 0.936–1.00) for dementia. Internal consistency was high (Cronbach's α 0.884) and inter-rater reliability was excellent (intra-class correlation coefficient 0.905, 95% CI 0.804–0.964). Conclusion: The low-literacy adaptation of the ADAS-Cog had good psychometric properties in this setting. Further evaluation in similar settings is required.